2015
DOI: 10.1039/c5cc06471f
|View full text |Cite
|
Sign up to set email alerts
|

A novel AgNP/DNA/TPdye conjugate-based two-photon nanoprobe for GSH imaging in cell apoptosis of cancer tissue

Abstract: In the present study, a novel two-photon nanoprobe has been developed and successfully applied in glutathione (GSH) imaging in cell apoptosis of cancer tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…It should be noticed that the other thiol-containing amino acids such as Cys and Hcy can also cause a slightly decreased for absorbance signal. However, the cellular levels of Cys and Hcy are extremely low, whose levels are thousand times lower than that of GSH, 34 days, and the RSD is 2.5 % calculate by the absorbance at 651 nm (n=10). These results showed good stability of our assay.…”
Section: Optimization Of Sensing Conditionsmentioning
confidence: 99%
“…It should be noticed that the other thiol-containing amino acids such as Cys and Hcy can also cause a slightly decreased for absorbance signal. However, the cellular levels of Cys and Hcy are extremely low, whose levels are thousand times lower than that of GSH, 34 days, and the RSD is 2.5 % calculate by the absorbance at 651 nm (n=10). These results showed good stability of our assay.…”
Section: Optimization Of Sensing Conditionsmentioning
confidence: 99%
“…With the continuous development of nanomaterial preparation technology, more and more emerging nanomaterials, combining with multiphoton imaging, have been applied in the field of biomedical photonics. With the unique properties of nanoprobes, multiphoton imaging can not only detect tumor cells [82] and apoptotic cells, [83,84] but also present the process of endocytosis of nanoprobes in detail. [92,93,96] Yu et al prepared ZnS:Mn by a simple Lewis acid-base reaction method, which exhibited good three-photon excitation performance.…”
Section: Disease Diagnosis Imagingmentioning
confidence: 99%
“…[ 82 ] Tang et al observed 3D images of fresh cervix tumor tissue from 0 to 300 µm using the DNA/AgNP/TPdye nanoprobe. [ 83 ] The fluorescence signals at a depth of 300 µm were also detected in the liver tissue sections of mice through the AuNP/peptide‐TPdye nanoconjugate. [ 84 ] Zong et al prepared DCzPDI with typical aggregation‐induced emission characteristics.…”
Section: Low‐dimensional Nanomaterials For Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Scheme , a carbazole derivative, ethyl-4-[3,6-bis­(1-methyl-4-vinylpyridium iodine)-9 H -carbazol-9-yl)] butanoate (EBMVC-B), was synthesized, and could rapidly intercalate into DNA grooves with bright fluorescence, due to its large flat aromatic structure and cationic charges (Figure S1). We found that the fluorescence of the fluorophore/DNA could be high-efficiently quenched by the in situ formed CuNPs on DNA scaffold; attractively, when the quenched EBMVCB/DNA-CuNPs were introduced into a CN – -contained system, CuNPs could be etched by CN – based on an Elsner-like reaction, resulting in fluorescence recovery. The lighting of fluorescence could be achieved in 2 s, and thus, a nanolamp was rationally constructed for instantaneous monitoring of CN – .…”
mentioning
confidence: 95%